Partographic comparison of spontaneous labour with oxytocin and prostaglandin induced labour - Hurakadli, Kirti M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To study the cervimetric progress (pattern) of labor in primi gravid women with spontaneous labor and in those with labor induced with oxytocin, oral misoprostol (25 µg) and vaginal misoprostol (25 µg) and to suggest, one nearer the best inducing agent. Methods: 100 primigravida women with singleton pregnancy with vertex presentation either in the latent phase of spontaneous labor or having an indication for induction were included in this study. They were divided into four equal groups of 25 each, and induced with oral misoprotol (25 µg), vaginal misoprostol (25 µg) and oxytocin. Fourth group was allowed for spontaneous labor. Main outcome measures studied were Success rate. Induction - delivery interval, mode of delivery and maternal and fetal complications. The quantitative data, comparison was performed using the chi-square test with Yates’s correction, students‘t’ test and analysis of variation. Group averages were reported as mean±standard deviation. Results: Mean induct ion delivery interval was significantly shorter in the oxytocin group and oral misoprostol. The pattern of cervical dilation in the oral misoprostol group closely followed the partographic curve of spontaneous labor. Cesarean rates were higher in the oxytocin group when compared to oral and vaginal misoprostol group. Uterine tachysystole was seen in 2 cases of oxytocin group when compared to one case in the vaginal misoprostol group. Conclusions: Oxytocin was a better inducing agent with respect to shorter induction to delivery time, maternal complications. Oral misoprostol showed a lot of promise in the dosage and frequency used the ease of administration, success rate, and fewer perinatal and maternal complications.